Development of a Mixed Reality Based Learning Application for Microcontroller Education Using the Luther Sutopo Multimedia Development Method - Antoni Pribadi; Ratu Natalia Marjani Ufayrah; Andri Nofiar. Am; Nurkholis Nurkholis; M. Alkadri Perdana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid advancement of immersive technologies has created new opportunities to improve learning effectiveness, particularly in technical education such as microcontroller systems. Conventional teaching methods still rely heavily on static visualizations and theoretical explanations, which limit students' ability to understand complex hardware interactions. A mixed reality (MR)-based learning application was developed to improve students' conceptual understanding of microcontroller components and their functions in an interactive and immersive environment. The development process followed the Luther–Sutopo multimedia development method, consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The application was built using Unity and Blender and deployed on the Oculus Meta Quest 2 platform. Usability testing involved 10 vocational students with prior knowledge of microcontrollers. The application achieved an average usability score of 4.54 out of 5 (90.8%), placing it within the